TANGGUNG JAWAB BIRO PERJALANAN WISATA TERHADAP KERUGIAN YANG DIALAMI OLEH KONSUMEN PENGGUNA JASA - Yogi Puspakanta, Ida Bagus; Dirksen, A. A. Ngurah Gede; Dharma Kusuma, A. A. G. Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014, 2014)
In performing its role, tourism industry must apply concept, regulation, and reference which are valid in tourism development in order to be able to maintain and enhancet the number of touristvisit that will end at the economic advantages for tourism industry and local people. In the relation with the formation of management, performance, change and dismissial of tourism buisness, there is a law stipulatiom for companies in general. The constitution, the Undang-Undang number 10 Year 2009 does not specifically rule the tourism business organiztions, and there should be a section, Pasal 14, the constitucion, the undang-Undang Number 10 Year 2009 on tourism, meanwhile oard the exsistence and the form of the tourism travel bureau is ruled in the constitucion, the Undang-Undang Number 40 Year 2007 on the Limited Company because based on the regulation of Government of the Republic of Indonesian Number 67 Year 1996 on the Tourism Performance. Paragraph 1 section 10 on Travel Bureau Service mentions that tourism travel bureau must vbe in the form of limited companies.
Keywords: Tourism Travel Bureau